An analysis on Bank Loan Loss provisioning behaviour in China - LIU, HUIQIN (2017)
The aim of this study is to investigate the loan loss provisioning behavior of Chinese bank. It uses an unbalanced panel data of 118 banks with 336 observations over the period of 2012-2016, using the General Moment methodology and Stochastic Frontier analysis methodology. Based on previous studies on earning management, capital management and business cycle hypothesis, X-efficiency is included as a determinant and it proved to be an variable which can affect the LLP behavior. The result of this study strongly support the capital management hypothesis and showing a counter-cyclical provisioning practice in Chinese banking sector. However, we do not find significant evidence supporting the earning management hypothesis.